LVIV TELEVISION: PROBLEMS AND CHALLENGES - Yuliana Kazimova (Інтегровані комунікації, 2025)
The study of the problems of Lviv television is important because Ukrainian television, in general, has repeatedly encountered a number of difficulties in the process of its activities, which continue constantly, but to different degrees, because problems arise in accordance with changes and demands of society. Lviv television, in particular, in addition to the general problems known to Ukrainian television, has had its own special problems. In addition to general difficulties such as the problem of maintaining objectivity, honesty, compliance with ethics, competition between traditional television and Internet television, and the bias of television channels, there are also problems of purely Lviv television, such as reforming the television channel, the process of dismissing journalists, changing the names and management of the television channel, as well as confusion between the television channel, which is now called "Suspilne Lviv" with "Lviv-TV" and modern challenges of television.